Polymorphisms in glucocorticoid receptor gene: a susceptibility factor to Guillain-Barré syndrome in a Bangladeshi population - Khurshid, Sarah (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.